OCCUPATIONAL SAFETY AND HEALTH HAZARDS OF APPAREL SECTOR: PERSPECTIVE OF NORTHERN PROVINCE EMPLOYEES OF SRI LANKA - THATSHAYINI, P.; RAJINI, P.A.D. (University of Jaffna, 2018)
Occupational Safety and Health (OSH) is an important aspect which allows an organisation to systematically manage the safety and health of the workers in a workplace. Adoption of OSH in a work environment therefore helps for the promotion and maintenance of the highest degree of physical, mental and social wellbeing in all occupations. Literature reveals that the apparel sector’s working environment is mostly associated with different kinds of workers, machinery and management teams and therefore, it should be safe and free from safety and health risks and hazards. Although there is a growing concern on OSH hazards, a lack of attention has received for researches on OSH in Sri Lankan context. Further, researches conducted on OSH in Northern in Sri Lanka are hardly found. Hence, the aim of this research is to investigate the level of exposure of employees working in apparel manufacturing organisations in Northern Province of Sri Lanka to different OSH hazards.A comprehensive literature review identified 31number of OSH hazards of apparel sector in the global and local contexts and the levels of exposure of the employees to those hazards were identified through a questionnaire survey. The data were collected from 76 number of employees working in eight different apparel manufacturing organisations in Northern Province of Sri Lanka. The collected data were analysed using RII (Relative Importance Index) method. As the study revealed, the hazards to which the apparel manufacturing employees in Northern Province of Sri Lanka are mostly exposed to are “excessive noise”, “repetitive nature of works”, “stress”, “excessive exposure to cotton dust” and “taking imbalance diet” under physical, ergonomic, psychological, chemical and biological hazard categories respectively.
Keywords: Occupational Safety and Health (OSH); Hazards; Apparel Sector; Northern Province; Sri Lanka.